THE INFLUENCE OF SERVICE QUALITY, PERCEIVED VALUE, AND TRUST ON CUSTOMER CITIZENSHIP BEHAVIOR ON SHOPEE (A CASE STUDY ON MANAGEMENT STUDENTS AT FACULTY OF ECONOMICS AND BUSINESS, HALU OLEO UNIVERSITY, KENDARI) - Azis Muthalib, Dzulfikri; Sinarwaty, Sinarwaty; Conny, Conny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine the effect of service quality, perceived value, and trust on customer citizenship behavior on Shopee. The population in this study consists of students from the Management Department, Faculty of Economics and Business, Halu Oleo University, Kendari. This research is an explanatory study. The sample selection in this study used purposive sampling, with a total sample of 85 respondents. The data analysis method used in this study is multiple regression analysis. The results of this study indicate that: (1) Service quality has a positive and significant effect on Customer Citizenship Behavior (CCB). (2) Perceived value shows a positive effect on customer citizenship behavior (CCB), although this effect is not statistically significant. (3) Trust has a positive and significant effect on customer citizenship behavior (CCB).